2006
DOI: 10.1111/j.1556-4029.2006.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Illicit Indoor Cannabis Cultivation in The Netherlands

Abstract: To obtain a reliable estimation on the yield of illicit indoor cannabis cultivation in The Netherlands, cannabis plants confiscated by the police were used to determine the yield of dried female flower buds. The developmental stage of flower buds of the seized plants was described on a scale from 1 to 10 where the value of 10 indicates a fully developed flower bud ready for harvesting. Using eight additional characteristics describing the grow room and cultivation parameters, regression analysis with subset se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 3 publications
(5 reference statements)
5
32
1
1
Order By: Relevance
“…Since upon discovery, police has usually little clues on the precise nature of varieties used by growers, Toonen et al [5] could not account for variability in yield between different so-called cannabis strains. Vanhove et al [7] showed that the variety used is a main yield-determining factor in indoor cannabis production.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since upon discovery, police has usually little clues on the precise nature of varieties used by growers, Toonen et al [5] could not account for variability in yield between different so-called cannabis strains. Vanhove et al [7] showed that the variety used is a main yield-determining factor in indoor cannabis production.…”
Section: Introductionmentioning
confidence: 98%
“…The study results of Toonen et al [5] were based on discovery and confiscation of 77 indoor cannabis plantations for which yield was estimated at the spot. Since upon discovery, police has usually little clues on the precise nature of varieties used by growers, Toonen et al [5] could not account for variability in yield between different so-called cannabis strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instability of clusters in a region might follow the effectiveness of a police intervention or indicate resilience if a hotspot returns. In addition, spatial and temporal analysis are relevant for other jurisdictions that, like Quebec, have domestic producers of cannabis: other provinces of Canada (Ontario Association of Chiefs of Police, 2003), the United States (Hurley, West, & Ehleringer, 2010;Weisheit, 2011), the United Kingdom (Potter, 2006), New Zealand (Cocklin et al, 1999) and the Netherlands (Toonen, Ribot, & Thissen, 2006).…”
Section: Clusters As Hotspots and Coldspotsmentioning
confidence: 99%
“…This plant can be grown on every continent and almost in every country, whereas indoor growing, which has recently become more popular, also contributes to its expansion. In the last decades, there has been an increase of indoor growing of cannabis plant in many countries, which, apart from resulting in the greater yield, also has a significant effect on the chemical composition of the plant (TOONEN et al, 2006). The main psychoactive component of C. sativa is 7, 8, 9, 10-tetrahydro-6, 6, 9-trimethyl-3-pentyl-6H-dibenzo (b, d) pyran-1-ol, also known in forensic literature as (-)-trans-Δ 9 tetrahydrocannabinol, or simply tetrahydrocannabinol (THC) (BRENNEISEN, 2007).…”
Section: Introductionmentioning
confidence: 99%